ENHANCING VOCABULARY KNOWLEDGE - CM Simatupang, Ervina; Chairiawaty,; Dahlia, Anum (International Journal of Psychosocial Rehabilitation, 2020)
The effort to understand and speak English is not as difficult as people think. The development of mobile phones has contributed to understanding and speaking English easily with the invention of transliteration applications. This application helps people to improve and enhance their English ability, especially enhancing vocabulary knowledge. This study is aimed at investigating the effectiveness of transliteration applications in enhancing vocabulary knowledge. A transliteration application has been used as a travel dictionary by tourists to communicate with people they meet around the world. The writers analyzed that this application can be used to achieve the course learning that is increasing vocabulary knowledge. With the technology of smart phones, people have a big opportunity to learn what they want to know and master it. The method used in this study was descriptive-qualitative. The writers described and analyzed the data based on observation.